2023
DOI: 10.11591/ijece.v13i4.pp4087-4100
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing 3D model of accident scene using drone image processing

Abstract: At the current stage, an investigation technique on the accident takes a longer time and this causes longer traffic congestion. The aim of this study is to reconstruct a 3D model of an accident scene using an unmanned aerial vehicle (UAV). The flight parameters that have been chosen are the circular method, the double grid method, and the single grid method. All these designs can produce a good 3D model to achieve the study’s objective. The methodology in this study is divided into 4 phases which are prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Earlier studies have shown that neither the use of RTK drones [40] nor the application of GCPs improved horizontal accuracy significantly [41], and the differences typically remined below 5 cm. This level of accuracy is satisfactory for road accident investigation [31] (also see calculation below in Section 3.4).…”
Section: Introductionmentioning
confidence: 90%
“…Earlier studies have shown that neither the use of RTK drones [40] nor the application of GCPs improved horizontal accuracy significantly [41], and the differences typically remined below 5 cm. This level of accuracy is satisfactory for road accident investigation [31] (also see calculation below in Section 3.4).…”
Section: Introductionmentioning
confidence: 90%
“…The functions they execute in both commercial and civilian contexts are expected to progressively increase in complexity as time progresses. Here is a compilation of some of their existing capabilities [1], [5], [8], [10], [16], [34], [52]- [54], [59]: -Fully automated flights: Employing traditional techniques can pose difficulties when attempting to chart and monitor extensive regions. Nevertheless, drones equipped with pre-programmed flight routes have the capability to perform this task without the need for manual intervention.…”
Section: What Is the Future Of Military Drones?mentioning
confidence: 99%